Does Corporate Governance Affect the Critical Corporate Policies such as Dividend Policy? - Lin, Dan; Lin, Lu (International Journal of Economics and Financial Issues, 2020)
This study examines the influence of corporate governance on dividend policy based on a sample of Canadian firms listed on the S&P/TSX composite index during 2009-2012. The results show that firms with better governance quality, measured by the governance index provided by The Globe and Mail, have larger payouts and have a higher propensity to pay dividends. In terms of four dimensions of corporate governance index, the shareholding and compensation index is the most important determinant of dividend payouts. Our results support the complementary role of corporate governance and dividend policy of the firms. The implication from this study is that managers and board of directors should make dividend payout decisions in a big picture of corporate governance. Keywords: Dividend Policy, Corporate Governance, Agency Problem JEL Classifications: G30, G34, G35 DOI: https://doi.org/10.32479/ijefi.10546